Можливості заміщення природного газу вугіллям власного видобутку - Stohniy O.V.; Kaplin M.I.; Makarov V.M.; Bilan T.R. (General Energy Institute of the National Academy of Sciences of Ukraine, 2014)
The article presents a basic methodological approach to feasibility study for the substitution of natural gas with local coal products in the national economy, including assessment of consumption volumes. The proposed substitution pivots on an attainable rate of growth in production of coal of required ranks and quality, enabled by all possible growth areas for the domestic fuel bases.A rating model is proposed for gradual switching from gas to coal fuel. Ratings for replacing gas technologies are determined in a model based on ecological sustainability and cost of introduction of coal technologies.Economic reforms in Ukraine may result in increasing local coal mining up to 100.27 million tons in 2020. Benchmarking the performance of coal and gas sectors shows a potential for Ukraine to meet its natural gas demand by replacing 12.7 bcm of natural gas with coal fuel. Producing 20 bcm of its own gas, Ukraine has to import 18.3 bcm, which could come as reverse flow supplies from European countries.Assortment aspect of natural gas substitution shifts the fuel deficiency issue to the domain of increased coal imports. This offers much wider opportunities for diversification of supplies from world coal markets as compared with natural gas markets.